A 3-year retrospective study of clinical durability of bulk-filled resin composite restorations - Muhittin Ugurlu; Fatmanur Sari (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to assess the clinical longevity of a bulk-fill resin composite in Class II restorations for 3-year.Materials and MethodsPatient record files acquired from the 40 patients who were treated due to needed 2 similar sizes Class II composite restorations were used for this retrospective study. In the experimental cavity, the flowable resin composite SDR was inserted in the dentinal part as a 4 mm intermediate layer. A 2 mm coverage layer with a nano-hybrid resin composite (CeramX) was placed on SDR. The control restoration was performed by an incremental technique of 2 mm using the nano-hybrid resin composite. The restorations were blindly assessed by 2 calibrated examiners using modified United States Public Health Service criteria at baseline and 1, 2, and 3 years. The data were analyzed using non-parametric tests (p = 0.05).ResultsEighty Class II restorations were evaluated. After 3-years, 4 restorations (5%) failed, 1 SDR + CeramX, and 3 CeramX restorations. The annual failure rate (AFR) of the restorations was 1.7%. The SDR + CeramX group revealed an AFR of 0.8%, and the CeramX group an AFR of 2.5% (p > 0.05). Regarding anatomical form and marginal adaptation, significant alterations were observed in the CeramX group after 3-years (p < 0.05). The changes in the color match were observed in each group over time (p < 0.05).ConclusionsThe use of SDR demonstrated good clinical durability in deep Class II resin composite restorations.